Correction: Zannella et al. Antiherpetic Activity of Taurisolo®, a Grape Pomace Polyphenolic Extract. Microorganisms 2023, 11, 1346 - Carla Zannella; Annalisa Chianese; Giuseppe Annunziata; Annalisa Ambrosino; Anna De Filippis; Gian Carlo Tenore; Ettore Novellino; Mariano Stornaiuolo; Massimiliano Galdiero (Microorganisms)
In the original publication [...]